(untitled) (Research, Society and Development, 2022)
Our objective is to identify, gather and synthesize studies on the Food and Nutrition Security of the homeless population, through a scope review. We designed this protocol based on the method proposed by the Joanna Briggs Institute (JBI) and registered it in the Open Science Framework (OSF) repository. To achieve the objective, we will guide our search for articles in the databases based on the guiding question: What are the themes, research approaches, places of origin, main results and conclusions in research on Food and Nutrition Security for a population in of street? We will use Rayyan software for the organization and selection of studies, carried out by two reviewers guided by the inclusion and exclusion criteria. If necessary, in case of discrepancies, a third reviewer will compose our team at this stage. We will present the data in a descriptive way according to the PRISMA-ScR checklist. We hope that the scope review will contribute to other research and interventions that involve the homeless population in the perspective of guaranteeing food and nutritional security.